A struggling international partnership: TNK-BP joint venture. (10th March 2009) - Ekin, A. Cemal; King, Thomas R.
Joint ventures with equity participation by partners bring together parties with different capabilities to achieve a common goal. The expectation typically focuses on synergy that will benefit both parties. BP, the British oil company and the Russian conglomerate TNK formed a joint venture with similar hopes. BP offered its significant market power in the world and technological know-how; TNK brought to the table the vast oil reserves in the steppes of Siberia. In a few short years, the venture started manifesting instability primarily caused by the differences in economic motives and cultural orientations of the partners. This paper traces the chronology of events in the souring relationships between the partners as evidenced in recent times and assesses the instability of the venture.